Preparation of Low Glycemic Rice and Comparison of Its Physicochemical Properties, Cooking Characteristics, Starch Digestibility and Microstructure with Raw Rice (Swarna Cv) - Yadav, Gorenand Prasad; Dalbhagat, Chandrakant Genu; Mishra, Hari Niwas (Food Science and Engineering, 2022)
Rice broken and low glycemic ingredients such as millet and pseudocereal were used to formulate the multigrain flour using Linear Programming (LP) in MATLAB to prepare Low Glycemic Rice (LGR). The constraints considered in LP were: glycemic index (GI < 55), protein (≥ 10 g/100 g), iron (≥ 6 mg/100 g) and carbohydrate (≤ 70 g/100 g). A laboratory-scale co-rotating twin-screw extruder was used to produce the LGR. Proximate composition, mineral content, physicochemical properties, cooking characteristics, starch digestibility, pasting properties and microstructure of LGR were analyzed and compared with raw rice (Swarna Cv.). The LGR was characterized as a highly nutritious low glycemic food (GI value of 55.03) with high protein (12.88%), fiber (2.22%), fat (2.28%), ash (1.38%), and iron content (16.11 mg/100 g) as compared to the raw rice. The cooking losses (14.23%), water solubility index (7.21%) and total colour difference (25.14) of LGR were significantly higher, whereas cooking time (8.25 minutes) was significantly lower, which may be due to several cracks and voids as observed in SEM analysis. Moreover, the LGR showed significantly different pasting properties compared to raw rice.